To Weight or Not To Weight? A Statistical Analysis of How Weights Affect the Reliability of the Quarterly National Household Survey for Immigration Research in Ireland - Nguyen, Nancy Duong; Murphy, Patrick (The Economic and Social Review, 2015)
Ireland has an immigrant population that is proportionally among the largest in the EU. Considering the impact this has had on Irish society, a surprisingly small amount of quantitative research has been performed to date. This paper evaluates the effectiveness of the weighting schemes associated with the Quarterly National Household Survey (QNHS), the primary data source for immigration research in Ireland. This is the first time that the QNHS weighting mechanism has been formally evaluated in the literature. Our analysis shows that there are significant issues relating to the weighting mechanism. This has major consequences for quantitative research on immigration in Ireland.